Chronic disease prevalence and preventive care among Ontario social housing residents compared with the general population: a population-based cohort study - Brar, Jasdeep; Agarwal, Gina; Keshavarz, Homa; Angeles, Ric; Pirrie, Melissa; Marzanek, Francine; Nguyen, Francis; Paterson, J Michael; Koester, Christie; Mahal, Guneet; Plishka, Mikayla; Popal, Sahar; et al. (My University, 2025)
Background: Older adults living in social housing report poor health and access to healthcare services. This study aimed to estimate the prevalence of chronic diseases, influenza vaccination and cancer screenings among social housing residents versus non-residents in Ontario, Canada. Methods: We conducted a population-based cohort study for all health-insured Ontarians alive and aged 40 or older as of 1 January 2020. Social housing residents were identified using postal codes. Validated health administrative data case definitions were used to identify individuals with diabetes, hypertension, chronic obstructive pulmonary disease, asthma, congestive heart failure and cardiovascular disease. Influenza vaccination and mammography, Pap and colorectal cancer screenings were identified among screen-eligible residents using health administrative data. Results: The prevalence of all chronic diseases was higher among social housing residents across all age groups: 40-59, 60-79 and 80+ years. Influenza vaccination rates in 2018-2019 were lower among social housing residents aged 60-79 and 80+ years. Mammography rates for women aged 50-69 years in 2018-2019 were 10-11% lower among social housing residents across all age groups compared with non-residents. Pap screening rates for women aged 40-69 in 2018-2019 were 6-8% lower among social housing residents. The percentage of colorectal screening in both women and men aged 52-74 was lower (9-10% in men and 6-7% in women) in social housing compared with the general population in 2019-2020. Conclusion: There is a higher prevalence of chronic diseases and lower cancer screening rates among the growing population of older adults in social housing in Ontario, Canada.
An infographic presenting the results of the following peer-reviewed publication: Agarwal G, Keshavarz H, Angeles R, Pirrie M, Marzanek F, Nguyen F, Brar J, Paterson JM. Chronic disease prevalence and preventive care among Ontario social housing residents compared with the general population: a population-based cohort study. J Epidemiol Community Health. 2025 Jan 28:jech-2024-222762.
Keywords: Social Housing; Vulnerable Populations; chronic disease; epidemiology; prevention; screening